2013
DOI: 10.1016/j.urology.2012.08.068
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Penile Size and Treatment Regret in Men With Recurrent Prostate Cancer After Surgery, Radiotherapy Plus Androgen Deprivation, or Radiotherapy Alone

Abstract: OBJECTIVE To report the relative incidence of the perceived reduction in penile size across prostate cancer treatment modalities and to describe its effect on quality of life and treatment regret. MATERIALS AND METHODS The incidence of patient complaints about reduced penile size was calculated for 948 men in the Comprehensive, Observational, Multicenter, Prostate Adenocarcinoma (COMPARE) registry who experienced biochemical failure (per registry definition) and were assessed a median of 5.53 years after pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 9 publications
0
25
0
2
Order By: Relevance
“…One novel concept identified in the study, genital atrophy, appears to be very common, yet this adverse effect has only recently been defined in the literature. 18 Results from this study were used to develop a comprehensive conceptual model depicting the impacts of prostate cancer and its treatment. Conceptual models are useful for identifying key endpoints for clinical studies, as well as for developing or selecting PROs to assess key endpoints.…”
Section: Discussionmentioning
confidence: 99%
“…One novel concept identified in the study, genital atrophy, appears to be very common, yet this adverse effect has only recently been defined in the literature. 18 Results from this study were used to develop a comprehensive conceptual model depicting the impacts of prostate cancer and its treatment. Conceptual models are useful for identifying key endpoints for clinical studies, as well as for developing or selecting PROs to assess key endpoints.…”
Section: Discussionmentioning
confidence: 99%
“…The 2017 study reported that 42% of participants reported more than 1 cm subjective PLS. 4A 2013 study by Parekh and colleagues of men (n = 948) mostly aged between 60-80 who reported selfperceived PLS (35). The study participants consisted of 22, 5% RT participants.…”
Section: Prevalence Of Penile Sensory Changes; Penile Deformity and Pmentioning
confidence: 99%
“…A 2018 study based their results on the physical measurement of PLS (32). Parekh et al;(2013) reported in their study that physicians completed a questionnaire based on their patients, one question noted under the complaints section referred to reduced penile size (35). No physical measurements were reported on.…”
Section: Penile Length Shorteningmentioning
confidence: 99%
See 2 more Smart Citations